DETEKSI DINI KANKER PAYUDARA MENGUNAKAN PEMERIKSAAN PAYUDARA SENDIRI (SADARI) - Wita Asmalinda; Jasmi Jasmi; Desy Setiawati; Khusnul Khatimah; Edy Sapada (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT, POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN PALEMBANG, 2022)
Breast cancer prevention efforts with breast self-examination. The type of community service carried out is the Community Partnership Program (PKM) in the form of counseling and simulations to participants regarding BSE examinations. The activity was carried out at the Al-Ikhlas Mosque, Karang Dalo Village, Pagaralam using the lecture method and simulation/demonstration of the BSE examination with 32 participants. This community service activity was carried out for 3 days which was used for training preparation in the form of obtaining a community service permit to the relevant institution, namely RT 002 RW 003 Karang Dalo Village as a land for community service implementation, preparing places, facilities and training tools as well as consumption and meals. afternoon for participants and organizers of training activities. Of the 32 participants, all of them were able to follow the training process until it was finished, namely from 09.30 WIB to 12.00 WIB. It can be concluded that there is an effect of counseling and examination of women of childbearing age regarding breast self-examination